Increasing the MSMEs performance through cutting edge innovation capability - Siregar, Muhammad Yamin; Warsani Purnama Sari; Ahmad Prayudi; Alfifto (Jurnal Siasat Bisnis, 2025)
Purpose – This paper analyzes how to increase micro, small and medium-sized enterprises (MSMEs) performance through Cutting Edge Innovation Capability. Design/methodology/approach – This study’s population consists of all 84,758 MSMEs in North Sumatera. A purposive sampling approach was used to select the respondents, with closed question for a sample of 218 leading MSME owner-managers in North Sumatera using the structural equation modelling technique (PLS-SEM). The main MSMEs in North Sumatra with the the following the categories of products: culinary, handicrafts, fashion, coffee shops, bakeries, garment, and services.Findings – The findings of this study show that Cutting Edge Innova¬tion Capability has positive and significant effect on performance of MSMEs from data processing and hypothesis testing results. Cutting Edge Inno¬vation Capability is innovation capabilities that combine product innovation, process innovation, market innovation, and organi¬zation innovation as: Sensing Capability, Seizing Capability, Trans¬forming Capability, Break¬through Concept Capability, and Superior Marketing Capability.Research limitations/implications – There needs to be a more balanced composition of leading MSMEs data, not too much many in food and beverage MEMEs. The research data for this category is 103 MSMEs (47%) while others MSME categories are also in need innovation capabilities such as souvenirs, agribusiness, and services. Practical implications – Based on research results, as input for MSME manager, MSME business actors in efforts increasing the innovation capabilities of MSMEs in line with the Government’s wishes the Republic of Indonesia through the Ministry of Cooperatives and SMEs, target MSMEs can move up a class (scaling up), MEMEs can go international.Originality/value – Cutting Edge Innovation Capability is needed to improve the MSMEs performance. In line with previous research, Market Orientation and SME Performance needed to be mediated by marketing capabilities.